Our Museum of Colonialism: Indigenous Representations of Museography in the Colombian Caribbean - Londoño Díaz, Wilhelm (Jangwa Pana, 2023)
This article is a philosophical exploration of the logic of colonial object collection by Kogui communities in northern Colombia. As revealed in a recent publication, some elders of the Kogui community of the northern slopes of the Sierra Nevada de Santa Marta preserved what could be an ax and a sword used in the conquest campaigns of the region, which occurred in the first decades of the sixteenth century. The information collected on this practice of artifact conservation was gathered within the framework of a series of conversations with leaders of this Indigenous community in northern Colombia that took place between 2018 and 2019. In these conversations, the logic of conserving these objects in the framework of the Indigenous social movement's political project was specified. In this case study, we first review the analytical tools that allow us to shift our attention from the classical theories of how museums, archeology, and history are defined. Then, we present the Kogui case, which questions the hegemonic narratives of regional history.